On the influence of action preference on female players` gaze behavior during defense of volleyball attacks - Lüders, T.; Schorer, J.; Loffing, F. (Frontiers in Sports and Active Living, 2020)
Knowledge of an opponent`s action preference may affect visual anticipation of their action outcome. If an opponent acts (not) according to their purported preference, anticipation is facilitated (unaffected or harmed). The underlying perceptual-cognitive mechanisms of that effect remain unclear. Here we tested the hypothesis that players might change their gaze behaviour once provided with preference information. To this end, 27 female volleyball players anticipated the direction of attacks in two test blocks with 40 videos each. Videos were shown on a large screen and stopped 240 ms prior to hand-ball-contact. Participants simulated defensive reaction while their gaze was recorded using a mobile eye-tracker. One female attacker directed 75% of shots diagonally (25% longline), while another female attacker distributed shots equally to both directions. After block one, half of the participants were informed that either both attackers preferred diagonal shots in 75% of occasions (group PReferred) or that both attackers distributed shots equally across directions (group Non-PReferred). Analysis of decision behavior (i.e., proportion of diagonal decisions), but not prediction accuracy (i.e., proportion of correct predictions), revealed that those instructions led both groups decide differently according to the purported preferences from block 1 to block 2. Analysis of gaze behavior did not reveal group-specific effects across blocks or attackers with/-out action preference. Findings underline the influence of contextual information on anticipation, but they leave open whether the availability of contextual information similarly affects gaze behavior.